ANALYSIS OF NSP CONCEPT UNDERSTANDING OF FIFTH GRADE STUDENTS OF SDN BEDAHAN, LAMONGAN REGENCY - Sya'adah, Amanah Mardika Megi; Kharisma, Ahmad Ipmawan; Huda, Mochammad Miftachul (Journal of Elementary Education, 2025)
This study aims to analyze the level of understanding of the concept of NSP of grade V students at SD Negeri Bedahan. Concept understanding is an important foundation in the development of critical thinking and problem solving skills, especially in learning Natural and Social Sciences (ESS) which contains various natural and social phenomena. This study used a descriptive qualitative approach with data collection techniques through observation, interviews and documentation studies. The research subjects consisted of the fifth grade homeroom teacher and 32 fifth grade students. The results showed that students' understanding of the concept of NSP was low. The main factors that influence this condition are the dominance of the lecture method which makes students passive, the use of learning media in the form of textbooks and videos, although learning facilities are adequate but the use of interactive learning media is still minimal. In addition, students tend to memorize concepts without understanding the deep meaning, and are embarrassed and afraid to ask questions when experiencing difficulties. This study recommends the need for the use of interactive learning methods and the utilization of digital interactive learning media to increase students' understanding of NSP concepts.